Malaysian Stakeholder Perspectives on Suicide-Related Reporting: Findings From Focus Group Discussions - Ng, Yin Ping; Pheh, Kai Shuen; Panirselvam, Ravivarma Rao; Chan, Wen Li; Lim, Joanne Bee Yin; Lim, Jane Tze Yn; Leong, Kok Keong; Bartlett, Sara; Tay, Kok Wai; Chan, Lai Fong (Frontiers in Psychology, 2021)
Media guidelines on safe suicide-related reporting are within the suicide prevention armamentarium. However, implementation issues beleaguer real-world practice. This study evaluated the perspectives of Malaysian media community, persons with lived experience of suicidal behavior (PLE), and mental health professionals (MHP) on suicide-related reporting in terms of the impact, strategies, challenges, and the implementation of guidelines on safe reporting. Three focus group discussions of purposively sampled Malaysian media practitioners (n=8), PLE (n=6), and MHP (n=7) were audio-recorded, transcribed, coded and thematically analyzed. Inclusion criteria were: English fluency, no clinical depression or suicidal ideation (current), no recent previous suicide attempts or suicide bereavement. Three major themes emerged: (1) Unsafe Reporting; (2) Impact; and (3) Safe Reporting. Most described current reporting as unsafe by being potentially triggering to media users and may contribute to contagion effect. Positive impacts identified included raised awareness towards suicide and its prevention. Unsafe reporting was attributed to inadequate awareness, knowledge, and guidance, lack of empathy and accountability, job-related factors, popularity-seeking, lack of monitoring and governance, and information source(s) with unsafe content. Majority agreed on how suicide stories should be framed to produce a safe report. The media community diverged on how detailed a suicide story should be. Safe reporting challenges included difficulties in balancing beneficial versus harmful details, social media ubiquity and its citizen reporters. Participants suggested these safe reporting strategies: stakeholder engagement, educational approaches, improving governance and surveillance, and guidelines revision. Most acknowledged the relevance of guidelines but were unaware of the existence of local guidelines. Implementation challenges included the dilemma in balancing media industry needs vis-à-vis safe reporting requirements, stakeholder engagement difficulties and social media regulation. There is poor awareness regarding safe suicide-related reporting across all groups. PLE and MHP were negatively impacted by current unsafe messaging which aggravated trauma and grief reactions. Postvention support gaps for mental health professionals was highlighted. Safe reporting promotion strategies should include stakeholder engagement to increase awareness on minimizing Werther and maximizing Papageno effects. Strategic re-examination and dissemination of local media guidelines to address new media issues, and effective surveillance mechanisms, are crucial in sustainable improvement of safe reporting practices.